1993
DOI: 10.1016/0014-5793(93)80927-m
|View full text |Cite
|
Sign up to set email alerts
|

Uridylylation of the PII protein in Rhizobium leguminosarum

Abstract: Permeabilization with cetyl trimethyl ammonium bromide was used to study the post‐translational modification of the PII protein in Rhizobium leguminosarum. Upon incubation with radioactive UTP a single band was obtained after SDS‐PAGE and autoradiography. RNase resistance and snake venom phosphodiesterase sensivity showed that radioactivity was bound through a phosphodiester bond to a protein which was absorbed by an antiserum specific for the PII protein. Uridylylation of the PII protein was shown to be depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…This residue is highly conserved, being present in the GlnB and GlnK proteins of the proteobacteria and the actinobacteria. Uridylylation of P II proteins has been demonstrated in Rhizobium leguminosarum (40), Klebsiella pneumoniae (55), Azospirillum brasilense (47,50), Azotobacter vinelandii (196), Herbaspirillum seropedicae (20), and Azoarcus sp. strain BH72 (150) and suggested in Sinorhizobium meliloti (8) (114), and Corynebacterium glutamicum (104).…”
Section: Modification Of P II In Response To Nitrogenmentioning
confidence: 99%
“…This residue is highly conserved, being present in the GlnB and GlnK proteins of the proteobacteria and the actinobacteria. Uridylylation of P II proteins has been demonstrated in Rhizobium leguminosarum (40), Klebsiella pneumoniae (55), Azospirillum brasilense (47,50), Azotobacter vinelandii (196), Herbaspirillum seropedicae (20), and Azoarcus sp. strain BH72 (150) and suggested in Sinorhizobium meliloti (8) (114), and Corynebacterium glutamicum (104).…”
Section: Modification Of P II In Response To Nitrogenmentioning
confidence: 99%
“…In fact, P II is involved in the covalent (and reversible) modification of both NtrC (through phosphorylation) and GSI (adenylylation), and thus in the regulation of their activity (5,31,32,74,75). In S. meliloti, B. japonicum, and R. leguminosarum, glnB is cotranscribed with glnA (GSI), forming a glnBA operon.…”
Section: P II Regulatory Proteinmentioning
confidence: 99%
“…Hence, glnB expression in R. leguminosarum is N regulated (fourfold lower in NH 4 ϩ compared to NO 3 Ϫ ), while it is constitutive in enteric bacteria (for a review, see reference 84). The P II proteins of R. leguminosarum and S. meliloti, as in enteric bacteria, are subject to covalent uridylylation, which modulates their activity (6,32,159). The degree of uridylylation is high under N limitation and undetectable under N excess (32).…”
Section: P II Regulatory Proteinmentioning
confidence: 99%
“…The assay for P II uridylylation was performed according to Colonna-Romano et al (1993). Strains were grown in minimal media (RMM) containing glutamate as a nitrogen source.…”
Section: Construction Of Mutant Strains and Recombinant Plasmidsmentioning
confidence: 99%
“…Expression of the glnII gene, which is preceded by a characteristic σ&%-dependent promoter, is strictly regulated by NtrB\NtrC and most probably turned off in symbiosis (Shatters et al, 1989). It was shown that the P II protein, which is encoded upstream of glnA (Chiurazzi & Iaccarino, 1990), negatively controls the transcriptional activity of NtrC and that it is subject to uridylylation, suggesting the presence of a UTase\UR-activity also in R. leguminosarum (Amar et al, 1994 ;Colonna-Romano et al, 1993).…”
Section: Introductionmentioning
confidence: 99%